Analisis Korosi pada Sambungan Double Nipple Pompa Submersible di Universitas Muhammadiyah Yogyakarta - Bambang Riyanta , M. Al Aththar (Semesta Teknika, 2011)
Corrosion is the deterioration of metal or alloy due to electrochemical reactions with its surroundings. The current study was conducted to determine the types and causes of corrosion on the double nipple connection of submersible pump which is used to pump water flooding the generator room at Universitas Muhammadiyah Yogyakarta. Chemical composition test was conducted to determine the material characteristics. The type of corrosion was determined by visual observation and confirmed with microstructure test. Chemical composition test was also conducted to investigate the nipple surface whether it has already been corroded or not. The water flooding into the generator room was analyzed to dete4rmine its chemical composition. The result shows that the material of the nipple is dead mild steel consisting of 0.133% carbon. Selective corrosion occurs on the outersurface of the nipple destroying 96.6% of its galvanized coating, and further shifted into a bimetal corrosion which attack 0.14 mm or 5.1% of the nipple wall thickness. Differential aeration corrosion attacked the inner surface of the nipple wall, due to the presence of Cl which is observed in the flooding water.